Three new species of Achrysocharoides Girault (Hymenoptera: Eulophidae) parasitoids of Phyllonorycter spp. (Lepidoptera: Gracillariidae) on Acer platanoides and Robinia pseudoacacia - Hansson, Christer; Shevtsova, Ekaterina (Zootaxa, 2010)
Three new species of Achrysocharoides are described, one from northern Europe, A. platanoidae sp. nov., one from central Europe and the U.S.A., A. robiniae sp. nov., and one from the U.S.A., A. robinicolus sp. nov. The descriptions are based on material reared from microlepidopterans of the genus Phyllonorycter Hübner (Gracillariidae): A. platanoidae from P. platanoidella (Joannis) on Acer platanoides, and A. robiniae and A. robinicolus from P. robiniella (Clemens) on Robinia pseudoacacia (black locust). The new species are very similar to previously described species, A. platanoidae to A. acerianus (Askew), and A. robiniae and A. robinicolus to A. gahani (Miller), but they are shown here to differ from their sibling species both in biology and in external morphology. The host of A. robiniae and A. robinicolus, P. robiniella, is a serious pest on the black locust tree in Europe, and the descriptions with diagnoses of these two species, and their scientific names, introduced here will aid the biological control efforts of this pest.